Protecting Indigenous and Local Knowledge Through a Biocultural Diversity Framework (2022)
ABSTRACT: Indigenous and Local Knowledge (ILK) is intrinsically connected to knowledge holders’ worldviews and relationships to their environments. Mainstream rights-based approaches do not recognize this interconnection and are hence limited at protecting the integrity of ILK. This paper presents two cases in Colombia in which, by recognizing community-environment interconnections, the biocultural diversity framework advanced the protection of communities’ ILK. The first case draws on court findings that recognized Indigenous and Afro-descendant peoples’ biocultural rights and granted legal personhood to the Atrato River—a pioneering ruling in the American hemisphere. The second case involved participatory fieldwork with the Embera peoples in designing a biocultural community protocol, reinforcing their relationship with the forest and protecting their biocultural heritage. The two cases illustrate that the biocultural diversity framework is inclusive of Indigenous and local communities’ worldviews and is hence an essential tool for the development of culturally appropriate protective mechanisms for ILK.